Advances in Civil Engineering Select Proceedings of ICACE 2020 - Arthur, Scott; Saitoh, Masato; Pal, Sudip Kumar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book presents select proceedings of the 5th International Conference on Advances in Civil Engineering (ICACE 2020), covering basic civil engineering branches. The book covers some hands-on articles on different realistic problems in civil engineering. It highlights the current application of advanced civil engineering knowledge in developing countries. Various topics covered include construction and building materials, eco-friendly ground improvement, water and wastewater management, solid waste management, durability of concrete structures, various aspects of foundation engineering, transportation engineering & planning scenarios in developing countries, and highway materials. A few articles also discussed the advancement in civil engineering fields from global perspectives too. The book will be useful for professionals and researchers working in the area of civil engineering.
Changes In Quality Of Supplied Drinking Water From Sources To Households In Dhaka City -- Low Cost Iron Removal Technology From Groundwater Using Locally Available Materials -- Spatial Variability Of Metal Elements In Soils Of A Waste Disposal Site In Khulna: A Geostatistical Study -- Low-Cost Salinity Treatment For Drinking Purpose Using Indigenous Materials -- Development And Characterization Of Novel Mn-Fe-Sn Ternary Nanoparticle By Sol-Gel Technique -- Potential Utilization Of Textile Dyeing Sludge, Pet Granules And Fly Ash In Lightweight Concrete Block.
Keywords: Buildings -- Design and construction; Construction industry -- Management; Building materials; Building Construction and Design; Construction Management; Building Materials; Civil engineering -- Congresses